The geomagnetic storm of August 2010 as a lesson of the space weather modeling - Miloš REVALLO; Fridrich VALACH; Magdaléna VÁCZYOVÁ (Contributions to Geophysics and Geodesy, 2010)
A model of the magnetic storm of August 4, 2010, is presented in the paper. Simulated Dst index series is obtained from an empirical model of the solar wind magnetosphere interaction and is compared with real data. In broader context, the underlying study can be conceived as an example of the space weather modeling. A brief survey of the approaches to this topic is provided in the paper. In particular, the link is made to the previous studies based on artificial neural networks which could be beneficial for the magnetic storm modeling as well.